A Longitudinal Cohort Study Investigating Inadequate Preparation and Death and Dying in Nursing Students: Implications for the Aftermath of the COVID-19 Pandemic - Galvin, John; Richards, Gareth; Smith, Andrew Paul (Frontiers in Psychology, 2020)
Aims and objectives To investigate how changes in the levels of preparedness and experiences of death and dying influence nursing students’ mental health. Background The COVID-19 pandemic is likely to cause significant trauma in the nursing population. The lack of preparation, in combination with a substantial loss of life, may have implications for the longer-term mental health of the nursing workforce. Nursing students have, in many cases, been an important part of the emergency response. Design A longitudinal cohort study was conducted in the academic year 2014/15 with data collected at two time points. There was a seven-month time period between data collection. Methods Participants completed paper-based questionnaires measuring demographics, academic stressors, clinical stressors, and mental health. 358 nursing students at time point one and 347 at time point two (97% retention) completed the survey. Results Inadequate preparation (OR: 1.783) and the inadequate preparation x death and dying interaction term (OR: 4.115) significantly increased risk of mental health problems over time. Increased death and dying alone did not increase mental health risk. Conclusions The results of this study suggest that it is not the increase in death and dying per se that causes mental health difficulties, but that it is instead the experience of high levels of death and dying in combination with inadequate preparation. The data are considered within the context of the COVID-19 pandemic, with both inadequate preparation and the scale of death and dying being two significant stressors during the emergency period.